ARACTÉRISTIQUES D’UN LOGICIEL INTERACTIF AVEC SPECTROGRAMME POUR LA CORRECTION PHONÉTIQUE AU SERVICE DES APPRENANTS ALGÉRIANOPHONES - Ilias Brahim; Soufiane Bengoua (Studii de gramatică contrastivă)
This study highlights a new interactive software with a spectrogram for phonetic correction aimed at Algerian learners. The objective is to address the difficulties related to the articulation of certain problematic French sounds, particularly the oral vowels absent from the Arabic vowel system. The software allows teachers to create personalized exercises, record students' productions, and visually compare their spectrograms to the target pronunciation through superimposition. A comparative study with the software Praat and Phon demonstrates the advantages of this tool in terms of ease of use, speed, individualization, and gamification. The results from a class of ten Algerian students underscore the pedagogical value for objectively assessing their progress, conducting a detailed analysis of oral production errors, and enabling collaborative phonetic remediation. Thus, the software provides a valuable tool for phonetic correction in French as a Foreign Language (FLE) classes, addressing the specific needs of teachers and their learners.